(untitled) (Research, Society and Development, 2020)
Introduction: Coronoid Process Hyperplasia (CPH) is an uncommon condition, characterized by hyperdevelopment of the coronoid process. The CPH mainly causing the limitation of mouth opening and may occur unilaterally or bilaterally. The aim of this article is to present a case of a male patient with bilateral Hyperplasia in the Coronoid Process. Case report: The patient compared the first appointment that it was not possible to open his mouth. Clinical examination revealed a 21mm mouth opening limitation, without facial asymmetries. On tomographic examination, hyperplasia of the coronoid process bilateral was observed. The patient underwent bilateral coronoidectomy surgery via the intraoral route, being followed up in the postoperative period by a multidisciplinary team. Discussion: A mandibular hypofunction caused by CPH can generate secondary changes that affect the patient, generating a negative impact on their daily routine. Final considerations: The importance of correct diagnosis and, consequently, of effective treatment strategies with a multidisciplinary team is emphasized.